Pain in Atopic Dermatitis: An Online Population-based Survey - Flavien Huet; Jason Shourick; Sophie Séité; Charles Taïeb; Laurent Misery (Medical Journals Sweden, 2020)
Pruritus in atopic dermatitis has been studied extensively; however, evaluation of skin pain has been very limited. The aim of this study was to evaluate the presence, frequency and characteristics of skin pain in patients with atopic dermatitis. A survey was conducted of a representative sample of 5,000 18-80-year-old individuals selected from the French population according to sex, age, geographical area and socioprofessional status. Data on socio-demographic status and the presence of any skin disease were collected. Pain in the past month and health-related quality of life were evaluated. Average intensity of skin pain during the previous month was assessed with a horizontal visual analogue scale (0-10). Skin pain was reported by more than half of the patients with atopic dermatitis, at a pain intensity of almost 6/10. A neuropathic component was suggested by the Douleur Neuropathique - 4 questions (DN4) questionnaire (a tool for detection of neuropathic pain), as well as the presence of pain inside and outside of skin lesions. Severe alterations to health-related quality of life were assessed with the Dermatology Life Quality Index and Short Form 12 Health Survey (SF-12). Pain is reported frequently by patients with atopic dermatitis. Healthcare professionals should question patients about pain and provide effective treatments. Future clinical trials must take skin pain into account.